2014
DOI: 10.1016/j.cmet.2013.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcription Factors Key for Mouse Pancreatic Development Establishes NKX2-2 and MNX1 Mutations as Causes of Neonatal Diabetes in Man

Abstract: SummaryUnderstanding transcriptional regulation of pancreatic development is required to advance current efforts in developing beta cell replacement therapies for patients with diabetes. Current knowledge of key transcriptional regulators has predominantly come from mouse studies, with rare, naturally occurring mutations establishing their relevance in man. This study used a combination of homozygosity analysis and Sanger sequencing in 37 consanguineous patients with permanent neonatal diabetes to search for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 58 publications
(38 reference statements)
5
87
0
Order By: Relevance
“…Interestingly, inactivation of Mnx1 in mouse causes dorsal pancreas agenesis because of deficiencies in the peripancreatic mesenchyme (Harrison et al, 1999;Li et al, 1999). However, in human, inactivating mutations in MNX1 cause permanent neonatal diabetes, to date without any evidence of exocrine pancreas failure, implying the primary site of dysfunction is more restricted to the β-cell (Bonnefond et al, 2013;Flanagan et al, 2014).…”
Section: Other Causes Of Permanent Neonatal Diabetes Reflecting Abnormentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, inactivation of Mnx1 in mouse causes dorsal pancreas agenesis because of deficiencies in the peripancreatic mesenchyme (Harrison et al, 1999;Li et al, 1999). However, in human, inactivating mutations in MNX1 cause permanent neonatal diabetes, to date without any evidence of exocrine pancreas failure, implying the primary site of dysfunction is more restricted to the β-cell (Bonnefond et al, 2013;Flanagan et al, 2014).…”
Section: Other Causes Of Permanent Neonatal Diabetes Reflecting Abnormentioning
confidence: 99%
“…Downstream of NEUROG3, four other transcription factors have been identified as causative for PNDM when mutated: NEUROD1 (Rubio-Cabezas et al, 2010), NKX2.2 , PAX6 (Solomon et al, 2009) and MNX1 (Bonnefond et al, 2013;Flanagan et al, 2014). The first three factors are expressed in human β-cells from early fetal development onwards (Lyttle et al, 2008;Jennings et al, 2013), with NEUROD1 and NKX2.2 considered to be direct targets of NEUROG3 action (Sussel et al, 1998;Gradwohl et al, 2000).…”
Section: Other Causes Of Permanent Neonatal Diabetes Reflecting Abnormentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these initial studies suggested that Mnx1 regulates β-cell differentiation and maturation. Furthermore, Mnx1 homozygous mutation was recently shown to cause permanent neonatal diabetes mellitus in humans (Bonnefond et al, 2013;Flanagan et al, 2014), suggesting a potentially conserved role of Mnx1 in β-cell function between mouse and human.…”
Section: Introductionmentioning
confidence: 99%